2018
DOI: 10.1111/eci.13014
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in heart failure with atrial fibrillation: Role of digoxin and diuretics

Abstract: An excess of mortality in HF patients with AF was found in a large retrospective community-based cohort. Digoxin and diuretics did not affect mortality in HF patients with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…and a study by Whitbeck et al (20) were both based on the same original trial database (Atrial Fibrillation Followup Investigation of Rhythm Management, AFFIRM), thus we only included the former because it had a rigorous analytic methodology and provided data on hospitalization in patients with AF using digoxin compared with those without digoxin. We finally included 29 studies (8-10, 14, 15, 17, 19, 21-42), in which there were 6 new studies (14,15,38,(40)(41)(42) different from previous version of systematic review (Figure 1). And a total of 621,478 patients were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and a study by Whitbeck et al (20) were both based on the same original trial database (Atrial Fibrillation Followup Investigation of Rhythm Management, AFFIRM), thus we only included the former because it had a rigorous analytic methodology and provided data on hospitalization in patients with AF using digoxin compared with those without digoxin. We finally included 29 studies (8-10, 14, 15, 17, 19, 21-42), in which there were 6 new studies (14,15,38,(40)(41)(42) different from previous version of systematic review (Figure 1). And a total of 621,478 patients were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of studies are summarized in Table 1. There were four studies (15,23,38,42) only included patients with AF with concomitant HF, while one study (32) only included patients with AF without concomitant HF. The remaining 24 studies included patients with AF regardless of concomitant HF.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, exercise training has been shown to improve heart function and prevent some heart diseases [25, 36, 61]. Numerous studies have reported that age-related heart disease is the leading cause of death in the elderly [62–64]. These findings suggest that cardiac function is important for mobility and survival in older individuals.…”
Section: Resultsmentioning
confidence: 99%
“…In young flies, cardiac dSir2 gene had no significant effect on climbing ability, and the reason for this may be that changes in heart function induced by cardiac Sir2 differential expression were not enough to cause hypoxia in tissues such as the brain [57, 58]. Cardiac Sir2 knockdown may contribute to age-related heart disease and lead to death in the elderly [62–64]. In addition, we found that exercise training improved the mobility in cardiac dSir2 differential-expression and old flies.…”
Section: Discussionmentioning
confidence: 99%
“…In Metaanalysen konnte bei Patienten mit VHF eine erhöhte Mortalität unter Digitalis nachgewiesen werden [26,27], randomisierte Studiendaten bei Patienten mit VHF und Herzinsuffizienz liegen jedoch nicht vor. Zudem konnte eine erhöhte Mortalität unter Digitalis nicht in allen Analysen bestätigt werden [28,29]. Dennoch sollte der Einsatz von Digitalis zurückhaltend erfolgen, d. h. nur bei therapierefraktärer Tachyarrhythmia absoluta.…”
Section: Therapieunclassified